A Study of Language across the Curriculum Pedagogy on Students’ Learning - Kapur, Kirti (INDIAN EDUCATIONAL REVIEW, 2020)
The study was undertaken to examine the role of language across the curriculum and to understand if, and how, classroom talk can help children learn to use language effectively as a tool for thinking collaboratively. It was conducted in the five representative schools of Delhi. The representative schools were KV, JNV, NDMC, RPVV and one private school, i.e., DAV. This pilot study was designed as a multi-phase experimental study. The key variables of ‘classroom talk’ and ‘critical thinking’ were studied through a mixed method approach. This included qualitative exploration using in-depth interviews, focus group discussions and field observation along with quantitative mapping of classroom practices. Both anecdotal and observed data contributed to the analysis of this study.